Intrauterine Resuscitation Therapy pharmacodynamics. - Mauad Filho, Francisco (2015)
The deficit in their environment met Maria fetal oxygen levels, causes the fetus to launch hand mechanism, within certain time limits, will give the necessary adaptation to environment protection and thereby enable effective. The mechanisms described include polycythemia, increasing the oxygen carrying capacity of the blood, placental level due to hypercapnia, allowing increased blood flow, and adapt the fetal circulatory system, the distribution of oxygen to the noble territories.